Comparative genomic and phenotypic analyses of the virulence potential in Shiga toxin-producing Escherichia coli O121:H7 and O121:H10 - Carter, Michelle Qiu; Laniohan, Nicole; Pham, Antares; Quiñones, Beatriz (Frontiers in Cellular and Infection Microbiology, 2022)
Shiga toxin-producing Escherichia coli (STEC) O121 is among the top six non-O157 serogroups that are most frequently associated with severe disease in humans. While O121:H19 is predominant, other O121 serotypes have been frequently isolated from environmental samples, but their virulence repertoire is poorly characterized. Here, we sequenced the complete genomes of two animal isolates belonging to O121:H7 and O121:H10 and performed comparative genomic analysis with O121:H19 to assess their virulence potential. Both O121:H7 and O121:H10 strains carry a genome comparable in size with the O121:H19 genomes and belong to phylogroup B1. However, both strains appear to have evolved from a different lineage than the O121:H19 strains according to the core genes-based phylogeny and Multi Locus Sequence Typing. A systematic search of over 300 E. coli virulence genes listed in the Virulence Factor DataBase revealed a total of 73 and 71 in O121:H7 and O121:H10 strains, respectively, in comparison with an average of 135 in the O121:H19 strains. This variation in the virulence genes repertoire was mainly attributed to the reduction in the number of genes related to the Type III Secretion System in the O121:H7 and O121:H10 strains. Compared to the O121:H19 strains, the O121:H7 strain carries more adherence and toxin genes while the O121:H10 strain carries more genes related to the Type VI Secretion System. Although both O121:H7 and O121:H10 strains carry the large virulence plasmid pEHEC, they do not harbor all pEHEC virulence genes in O121:H19. Furthermore, unlike the O121:H19 strains, neither the O121:H7 nor O121:H10 strain carried the Locus of Enterocyte Effacement, OI-122, nor the tellurite resistance island. Although an incomplete Locus of Adhesion and Autoaggregation (LAA) was identified in the O121:H7 and O121:H10 strains, a limited number of virulence genes were present. Consistently, both O121:H7 and O121:H10 strains displayed significant reduced cytotoxicity than either the O157:H7 strain EDL933 or the O121:H19 strain RM8352. In fact, the O121:H7 strain RM8082 appeared to cause minimal cytotoxicity to Vero cells. Our study demonstrated distinct evolutionary lineages among the strains of serotypes O121:H19, O121:H10, and O121:H7 and suggested reduced virulence potentials in STEC strains of O121:H10 and O121:H7.